1992
DOI: 10.1021/jm00097a011
|View full text |Cite
|
Sign up to set email alerts
|

6-Alkyl-12-formylindolo[2,1-a]isoquinolines. Syntheses, estrogen receptor binding affinities, and stereospecific cytostatic activity

Abstract: A number of 6-alkyl-12-formyl-5,6-dihydroindolol[2,1-a]isoquinolines were synthesized by the Bischler-Napieralski reaction from the respective 1-alkyl-2-(3-methoxyphenyl)ethylamines and bromo-substituted (methoxyphenyl)acetic acid chlorides followed by a second ring closure reaction involving a base-generated benzyne intermediate. The methoxy functions in positions 3 and 9 or 10 were cleaved with BBr3 and the free hydroxy groups converted into the acetates. The enantiomers of the most potent derivatives were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…In a previous paper we reported on the cytostatic activities and endocrine properties of a series of acetoxy-substituted 6-alkyl-12-formyl-5,6-dihydroindolo[2,1- a ]isoquinolines . Although these compounds bind to the estrogen receptor (ER), they did not show a preference for ER-positive cells when tested for cytostatic activity.…”
mentioning
confidence: 99%
“…In a previous paper we reported on the cytostatic activities and endocrine properties of a series of acetoxy-substituted 6-alkyl-12-formyl-5,6-dihydroindolo[2,1- a ]isoquinolines . Although these compounds bind to the estrogen receptor (ER), they did not show a preference for ER-positive cells when tested for cytostatic activity.…”
mentioning
confidence: 99%
“…As in previous studies [12] , we used the calf uterine cytosol as a convenient source of estrogen receptors. The RBA values of the new compounds ranged from 0.1 to 4.2 ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, studies on the biological activity of 5,6‐dihydroindolo[2,1‐ a ]isoquinolines have revealed promising results to advance in the treatment of manifold diseases. For instance, compounds 1 a and 1 b strongly inhibit tubulin polymerization and the growth of human breast cancer cells in vitro,, whereas compound 1 c is a melatonin agonist (Figure ) . Modern synthetic methods towards the 5,6‐dihydroindolo[2,1‐ a ]isoquinoline skeleton rely on the intramolecular cyclization of N ‐aryl‐1,2,3,4‐tetrahydroisoquinolines .…”
Section: Figurementioning
confidence: 99%